Trends and progress in studying butterfly migration. Issue 1 (12th December 2022) - Chowdhury, Shawan; Zalucki, Myron P.; Amano, Tatsuya; Poch, Tomas J.; Lin, Mu‐Ming; Ohwaki, Atsushi; Lin, Da‐Li; Yang, Li; Choi, Sei‐Woong; Jennions, Michael D.; Fuller, Richard A.
Abstract: Several hundred butterfly species show some form of migratory behaviour. Here we identify how the methodologies available for studying butterfly migration have changed over time, and document geographic and taxonomic foci in the study of butterfly migration. We review publications on butterfly migration published in six languages (English, Simplified Chinese, Traditional Chinese, Japanese, Korean, and Spanish), summarise how migration in butterflies has been studied, explore geographic and taxonomic patterns in the knowledge base, and outline key future research directions. Using English search keywords, we found only 58 studies from Asia; however, after searching in local languages, we found an additional 98 relevant studies. Overall, butterfly migration studies are mostly from North America and Europe. Most studies focus on three species: monarch ( Danaus plexippus ), painted lady ( Vanessa cardui ) and red admiral ( Vanessa atalanta ). About 62% of publications are focused on the monarch, with nearly 50% of migratory butterfly species mentioned in only a single paper. Several research methods have been applied to ascribe migratory status and to study the physiology, neurobiology, and ecology of migration; however, virtually all this research is on a handful of species. There remain hundreds of species for which we do not understand the comprehensive seasonal pattern of movement, flight destinations, wintering, or breeding grounds. A better understanding of movement ecology and migratory connectivity is needed to effectively conserve migratory butterflies. It is essential that research becomes more geographically and linguistically representative since migrants frequently cross political borders and international cooperation is necessary for their conservation. Abstract : We show (i) the potential importance of non‐English‐language literature for understanding butterfly migration globally, (ii) studies are mostly concentrated in North America and Europe with very few from the tropics, (iii) most studies are focused on three species: the Monarch ( Danaus plexippus ), Painted Lady ( Vanessa cardui ) and Red Admiral ( Vanessa atalanta ). There remain hundreds of species for which the full seasonal pattern of movement, flight destination, wintering or breeding grounds remain unknown. 摘要: 数百种蝴蝶具有迁徙行为。本研究总结了蝴蝶迁徙行为的研究方法变迁，以及展开相关研究的地域和蝴蝶类群格局。我们综述了六种语言（英文、简体中文、繁体中文、日文、韩文和西班牙文）发表的相关研究，总结了蝴蝶迁徙行为的研究方法、开展研究地域及具体研究类群，并建议了关于蝴蝶迁徙行为的主要研究方向。根据英文关键词搜索，共获得58篇来自亚洲的论文；但根据本地语言搜索，我们又获得了另外98篇来自该地区的论文。总体而言，蝴蝶的迁徙研究主要来自北美洲和欧洲。大多数研究集中于三个物种:黑脉金斑蝶（ Danaus plexippus ）、小红蛱蝶（ Vanessa cardui ）和优红蛱蝶（ Vanessa atalanta ）。约62%的论文主要研究黑脉金斑蝶，近50%的迁徙性蝴蝶仅在一篇论文中被提及。本研究查阅的论文采用多种方法研究蝴蝶的迁徙，包括生理学、神经生物学和生态学；然而，几乎所有研究只针对少数物种。因此我们对绝大多数迁徙性蝴蝶的季节性迁徙模式、迁徙目的地、越冬或繁殖地仍缺乏系统认识。为有效保护迁徙性蝴蝶，需更好地了解其运动生态学和迁徙连通性。由于蝴蝶的迁徙路径常常跨越国界，有必要展开更多的本地研究和国际合作。